PENYULUHAN HUKUM PERDATA DAN PIDANA BAGI APARAT KELURAHAN CEMPAKA BARU KEMAYORAN JAKARTA PUSAT - Derta Rahmanto; Endang Purwaningsih; Evie Rachmawati Nur Ariyanti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2017)
Promoting legal awareness to signify the importance of understanding the positive laws in Indonesia can be done through sustainable counselling programs. The poor legal awareness might result from the lack of legalawareness raising programs, the lack of public access to legal-related issues, and the less-supporting local culture. In attempts to better promote legal awareness, sustainable programs should start top-down, meaning the programs are first addressed to sub-district officers so that they can set good examples to their people. The curriculum should first highlight the overview of Indonesia’s legal system, followed by civil law and criminal law issues. These are fundamental for sub-district officers in Cempaka Baru Kemayoran Jakarta Pusat. These legal-awareness raising programscame in the form of lectures and trainings. To see the effectiveness, a pre-test and post-test were given to the participants. The conclusion suggests that—in attempts to better promote legal awarenessand knowledge for Cempaka Baru sub-district officers—periodical counselling on civil and criminal laws is essential. The curriculum should also include such topics as preventive and repressive measures in law enforcement. DOI: https://doi.org/10.26905/abdimas.v2i1.1292